The contribution of trust to academic knowledge sharing among academics in the Malaysian research institutions - Yaser Mutahar; Mazen Mohammed Farea; Mohammed Abdulrab; Yaser Hasan Al-Mamary; Adel Abdulmhsen Alfalah; Mohieddin Grada (Cogent Business & Management, 2022)
Knowledge sharing within the academic community is necessary for achieving academic excellence in today's knowledge-based environment. Knowledge sharing requires teamwork in research, collaboration and joint publications, which suggests building trust among academics. Thus, the present study develops a model based on the Theory of Social Exchange that addresses the contribution of trust to knowledge sharing. The study adopted a quantitative research design in collecting and analyzing data from 380 respondents who are academics in the five Malaysian research institutions. Structured equation modelling (SEM) via SmartPLS software was utilized to examine the study hypothesis. The results showed that trust (TR) has a positive and significant relationship with knowledge sharing (KS). Furthermore, trust significantly predicts organizational citizenship behaviour (OCB), which was found to influence KS significantly. Moreover, the study results show an indirect relationship between TR and KS. OCB variable's mediation effect is statistically significant. The current study establishes a link between trust and knowledge sharing. This area of research is limited in Malaysia, and research identifying the mediating role of OCB between trust and knowledge sharing behaviour within academic and research institutions in Malaysia is limited. The study's outcome applies to higher academic institutions and other academic and industrial corporations where knowledge sharing is required to ensure higher performance.
Keywords: 650; academics; higher educational institutions; knowledge sharing; Malaysia; Organizational Citizenship Behavior; research institutions; trust